Development planning to accelerate Sustainable Development Goals (SDGs) in Mahakam Ulu Districts as a new autonomous region - Bambang Irawan; Paisal Akbar; Eko Priyo Purnomo; Achmad Nurmandi (Faculty of Social and Political Science, Universitas Airlangga, 2021)
The new autonomous regions have been seen as a burden because many have not developed into areas that can build inclusive societies. The upstream area of the Mahakam River in 2013 bring forth a new autonomous region called the Mahakam Ulu Districts, and the study aims to describe development planning in the region. This research adopts a descriptive qualitative approach using secondary data. The research results show that the newly autonomous region of Mahakam Ulu Districts is a breath of fresh air for the people of the ideals of equitable development in their regions. Development planning has also upheld the SDGs’ goals; this can be seen from the programs that have been carried out, aiming to bring the Mahakam Ulu District prosperity and justice. The transformation of the values contained in the pillars of the SDGs has also felt to be present in the annual priority programs that have been carried out by Mahakam Ulu Districts, including in terms of social development, environmental development, economic development, and legal and governance development which continue to be pursued by all parties upstream of the Mahakam River, Mahakam Ulu Districts.